Efeitos da ractopamina, dos níveis de lisina digestível e dos métodos de formulação da dieta sobre o desempenho e características de carcaça de leitoas em terminação - Francisco Alves Pereira (2006)
Two experiments were conducted to evaluate the effects of ractopamine, lysine and feed formulation methods on performance and carcass traits of gilts in the finishing phase. The experiment I was conducted with 40 animals allotted in a completely randomize block design, in a 2x2 factorial scheme, two digestible lysine levels (DL) (0.67 e 0.87%) and ractopamine (0 and 5ppm). A significant effect of DL on the daily weight gain (DWG) and body weight (BW). Interaction among the DL level and ractopamine on feed;weight (FW) and lean carcass meat deposition (LCMD). Don’t was observed a significant effect of ractopamine on feed consumption (FC), DWG and BW. Don’t was observed a significant effect of DL level on the fat thickness (FT), muscle depth (MD) and lean carcass proportion (LCP), in agreement with the in vivo valuation. A significant effect of ractopamine was observed on FT in P2 point, until 21 days, LCP and MD in frigorific valuation. The experiment II was conducted with 60 animals allotted to the treatments in a completely randomize block design, in a 2x3 factorial scheme, two ractopamine level (0 and 5ppm) and three feed formulation methods. Was observed interaction among the Feed formulation method and ractopamine for DWG, BW , FW and LCMD. In agreement with the in vivo valuation, A significant effect of ractopamine was observed on FT, MD and LCP of the gilts. The ractopamine affected the proportion of the carré, FT and LCP, and don’t affected the dressing percentage, proportion of ham and MD.